Study of the association of the nutritional profile of pregnant women with the birth weight of newborns in Morocco - Houda Elfane; Sanaa El-Jamal; Khadija Sahel; Mohamed Mziwira; Mohammed El Ayachi; Rekia Belahsen (Roczniki Panstwowego Zakladu Higieny, 2021)
Background. Low birth weight (LBW) is an important predictor of neonatal morbidity and mortality. It reflects the nutritional status of the mother and the quality of health care services during pregnancy. Objective. The objective of this study is to determine the factors associated with low birth weight of children born to Moroccan pregnant women in the province of El Jadida. Material and Methods. This cross-sectional case-control study was carried out in the maternity ward of El Jadida provincial hospital on 344 parturient women, half of whom had given birth to children with an LBW and the other half of children with normal weight (NW) at birth. Information on maternal gestational and socioeconomic characteristics as well as eating habits was collected using a questionnaire and anthropometric measurements were taken on the newborns. Results. The study identified 172 parturient who gave birth to newborns with LBW and 172 parturient who gave birth to newborns of NW. The proportions of LBW are greater in first-time mothers (50.6%) and professionally inactive (86.6%). The mean weight of LBW newborns is 2013.95 ± 372.95g compared to 3380 ± 217.59g for NW newborns. The determined factors associated with LBW are the low socio-economic level (OR = 3.18; 95% CI: 1.09-9.23), insufficient monitoring of prenatal consultation (OR = 2.91; 95% CI: 1, 71-4.95), origin from rural areas (OR = 0.52; 95% CI: 0.30-0.91) and lack of nutritional education (OR = 0.17; 95% CI: 0, 09-0.34). The daily calcium intake in mothers of newborns with LBW is 33.82% of the recommended daily allowance (RDA), the daily iron requirement coverage was 50%, folates 66, 16% and zinc 87.72% of the RDA. Conclusions. Well-targeted and coordinated education and awareness-raising actions on early pregnancy and feeding pregnant women could have a positive impact on improving the birth rate of children with a weight deficit.